Participação social na coleta seletiva solidária - estudo de caso da Universidade Federal de Santa Maria - Freitas, Tiago Guterres de (2019)
Selective collection can be understood as the process of separation and collection of waste, previously separated in their origin according to its composition in organic, tailings and recyclables. Considering the need for an environmentally better destination for the waste generated by the Public Administration's own activity, the Federal Government published Decree no. 5,940, of October 25, 2006, instituting the separation of recyclable waste disposed of by the direct and indirect Federal Public Administration bodies and entities, at the generating source, and its destination to the associations and cooperatives of recyclable material collectors. Thus, the Solidary Selective Collection was established in the Federal Public Administration, creating the need for its organs and entities to adapt to this reality. Thus, the Federal Institutions of Higher Education (IFES) have a duty to implement the Solidary Selective Collection by adopting this new waste management model. The Solidary Selective Collection at the Federal University of Santa Maria (UFSM) began in 2016, so it is a recent experience. This action, in addition to providing an environmentally more appropriate treatment for waste, contributing to environmental sustainability, also brings improvements in the social field, ensuring employment and income for the families involved. In implementing the Solidary Selective Collection one of the fundamental aspects to ensure its consolidation is the effective participation of the generating sources. Accordingly, this Master's Dissertation was built with the general objective of analyzing social participation in the UFSM Solidary Selective Collection, with a view to contributing to social and environmental management actions in the search for the effective involvement of the academic community, through actions of environmental education. For the purpose of this research, a field study was carried out (UFSM) in order to carry out an exploratory research at the Center for Social and Human Sciences (CCSH). Thus, once the theoretical survey was performed, in the second moment, we used a survey to collect data involving subjects who answered a questionnaire sent online via the Institution's Questionnaire System. The main results achieved reveal that environmental sustainability aimed at preserving the environment, maintaining a clean campus and generating jobs and income for recyclers are important factors for the academic community to participate in the Solidary Selective Collection. In contrast, insufficient knowledge about this process by the academic community and gaps in awareness raising actions stand in the way of greater and more effective participation. Thus, based on these findings, actions were proposed aimed at the dissemination of the Solidary Selective Collection, to the awareness of the academic community, as well as to the training of the servers and students interested in deepening and disseminating the knowledge about the Solidary Selective Collection.